An Anomalous Right Coronary Artery Originating from the Left Anterior Descending Artery, a Case Report of Successful Percutaneous Coronary Intervention - Nematipour, Ebrahim; Shekari, Arash; Shirani, Shapour; Ghorashi, Seyyed Mojtaba (Acta medica Lituanica, 2025)
Background: An anomalous right coronary artery (RCA) originating from the left anterior descending artery (LAD) is a rare subtype of single coronary artery ostium. Revascularization in such cases is challenging due to the large feeding territory or the potential for compression by an adjacent vessel.Case description: We report the case of a 57-year-old woman who presented to our hospital with exertional chest pain and dyspnea. An anomalous RCA was identified, originating from the mid-portion of the LAD. Coronary angiography and coronary multi-detector computed tomography revealed a significant stenosis at the LAD just proximal to the RCA bifurcation. A successful percutaneous coronary intervention was performed to revascularize the LAD stenosis. The patient was discharged in good general condition two days later.Conclusions: Despite the rarity of coronary anomalies, future studies could be undertaken to assess the potential benefits of screening, particularly in specific populations such as professional athletes.